The Relationship Between HIV/AIDS Knowledge Levels and Teen Attitudes Towards Premarital Sex - Andreas Rantepadang; Brendsy Nessy Federika Pangau (Jurnal Penelitian Pendidikan IPA, 2024)
Adolescence is a stage characterized by rapid changes and challenges that can be difficult to face due to limited knowledge, particularly about HIV/AIDS. Knowledge plays a crucial role in shaping attitudes, which can influence changes in perceptions of premarital sex. The aim of this study is to examine the relationship between HIV/AIDS knowledge levels and teen attitudes towards premarital sex. The research employs a descriptive correlational method with a cross-sectional approach, involving 208 respondents selected through proportional stratified random sampling. Data collection was conducted using a questionnaire. The results revealed that 100 respondents (48.1%) fell into the adequate knowledge category, 90 (43.3%) were in the good knowledge category, and 18 (8.7%) were categorized as having poor knowledge. Regarding attitudes towards premarital sex, 198 respondents (95.2%) exhibited a positive attitude, while 10 (4.8%) displayed a negative attitude. The Spearman rank correlation test yielded a p-value of 0.05, indicating a significant relationship between knowledge and attitudes, with a very weak correlation in a positive direction. This means that as adolescents' understanding of HIV/AIDS increases, their attitudes become more positive. The study recommends adding resources about HIV/AIDS and premarital sex in schools and suggests that future research should focus on selecting appropriate educational methods for HIV/AIDS prevention.